Motivasi Kerja: Pengaruh Komunikasi Internal, Evaluasi, Reward pada Pt. Grab Teknologi Indonesia di Semarang - Achmad Junaidi; Wanuri Wanuri (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
Work motivation plays an important role in increasing employee productivity and job satisfaction. The problem that occurred was that there were a small number of employees at PT Grab Teknologi Indonesia who did not meet expectations. These employees show a lack of morale, abuse of break time, and have poor communication with their bosses and co-workers, which has an impact on low productivity. The purpose of this study is to find out and analyze the influence of internal communication, evaluation and rewards on employee work motivation at PT. Grab Teknologi Indonesia in Semarang. The population in this study is employees of PT. Grab Teknologi Indonesia in Semarang has 50 employees. The sampling technique used in this study is a saturated sampling technique or census or all population numbers are used as samples, but because there is 1 respondent as a researcher it is not used as a sample so that the results are not biased and the sample is set to 49 respondents. The data collection method in this study uses a questionnaire with an analysis method using multiple linear regression with t-test and F test as well as coefficient determination. The calculation results showed that the internal communication variable had a positive and significant effect on work motivation, the evaluation variable had a insignificant effect on work motivation, and the reward variable had a positive and significant effect on work motivation. The number of determination coefficients (Adjusted R Square) is 0.378. This means that the variables of internal communication, evaluation and reward have a role of 37.8% together to be able to explain or explain the variables of work motivation. Suggestions to improve internal communication at PT. Grab Teknologi Indonesia can include developing more effective communication channels, such as digital platforms for feedback, as well as regular team meetings to share information and achievements.